2017
DOI: 10.1007/s40273-017-0486-4
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluations of New Oral Anticoagulants for the Prevention of Venous Thromboembolism After Total Hip or Knee Replacement: A Systematic Review

Abstract: The economic analyses showed reasonable consistency in the model structures used and the events captured. The results strongly suggested that NOACs are cost effective alternatives to low molecular-weight heparin. Dabigatran appeared to be the least cost effective NOAC. More research is needed to assess the cost effectiveness of apixaban and edoxaban.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…To our knowledge, this is the first cost‐effectiveness analysis to compare multiple anticoagulants at several durations post‐TKA. Previous studies of anticoagulation therapy in TKA or THA recipients have focused on comparative analyses of 2 strategies or a single agent prescribed at different doses or durations . A cost‐effectiveness analysis by Schousboe and Brown showed that, when compared to LMWH, aspirin was the preferred strategy in THA patients but the cost‐effectiveness in TKA patients was dependent on age and DVT risk, with aspirin assuming a higher likelihood of cost‐effectiveness in older patients without high DVT risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first cost‐effectiveness analysis to compare multiple anticoagulants at several durations post‐TKA. Previous studies of anticoagulation therapy in TKA or THA recipients have focused on comparative analyses of 2 strategies or a single agent prescribed at different doses or durations . A cost‐effectiveness analysis by Schousboe and Brown showed that, when compared to LMWH, aspirin was the preferred strategy in THA patients but the cost‐effectiveness in TKA patients was dependent on age and DVT risk, with aspirin assuming a higher likelihood of cost‐effectiveness in older patients without high DVT risk.…”
Section: Discussionmentioning
confidence: 99%
“…Some research has suggested that longer anticoagulation regimens can substantially reduce the risk of DVT and PE ; however, in the absence of definitive recommendations, physicians are left weighing the risks of DVT and PE against those of anticoagulation therapy, including hemorrhage of gastrointestinal (GI) and central nervous system (CNS) sites, as well as a higher likelihood of prosthetic joint infection (PJI) . Prior cost‐effectiveness analyses evaluating anticoagulation therapy after joint arthroplasty have compared only 2 agents and few studies have considered the duration of therapy . One analysis evaluating prolonged (42‐day) versus standard (12‐day) treatment with enoxaparin in total hip arthroplasty (THA) or TKA patients suggested that prolonged therapy was cost‐effective in THA patients .…”
Section: Introductionmentioning
confidence: 99%
“…Findings reflect those from previous studies that have explored processes that influence implementation of ERAS for other conditions. 88,96,97 These found that multidisciplinary collaboration was essential and that this could be threatened by the need to co-ordinate working practices across different departments. 98 Likewise, components of ERAS were seen as incompatible with working practices of some members of the multidisciplinary team; this meant that some staff were resistant to change.…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…26,96 The importance of providing education and information to patients, and providing realistic expectations of their recovery, was discussed. 28,88 Temporality or strategies to embed ERAS over time were discussed in a small number of studies. 59 Studies have been synthesised in a recent systematic review.…”
Section: Overview Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation